Stanimir Panayotov in Conversation with Michael O’Rourke: “X, Welcome!!!” - Panayotov, Stanimir; O’Rourke, Michael (Identities: Journal for Politics, Gender and Culture, 2011)
Author(s): Stanimir Panayotov and Michael O’Rourke Title (English): Stanimir Panayotov in Conversation with Michael O’Rourke: “X, Welcome!!!” Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 2 (Summer 2011) Publisher: Department of Gender Studies, Euro-Balkan Institute Page Range: 97-135 Page Count: 39 Citation (English): Stanimir Panayotov and Michael O’Rourke, “Stanimir Panayotov in Conversation with Michael O’Rourke: ‘X, Welcome!!!,’” Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 2 (Summer 2011): 97-135.